Hepatitis C Patients with Progress of Disease Severity: Biochemical and Immunological studies (Journal of Nuclear Technology in Applied Science, 2020)
Hepatitis C infection has become epidemic with a rapid increase in the number of patients. Hepatitis C has some streaking among which are; most cases don't correlate with the histological of the hepatic biopsies of these patients. The present study aims at investigating some biochemical and immunological aspects among patients varying in degree of disease severity. The study includes 112 subjects; 24 healthy control and 88 CHC patients, grouped as follows: Group I: (control group), Group II: compensated chronic liver disease (without cirrhosis), Group III: decompensated with liver cirrhosis and Group IV: hepatocellular failure; end stage liver. Results of the present study showed that serum aspartate and alanine transaminases (AST & ALT), gamma glutamyl transferase (GGT), alkaline phosphatase (ALP) activities, total and direct bilirubin, globulin, AST/platelet ratio index (APRI), globulin/platelet ratio, tumor necrosis factor-α (TNF-a), interferon-g (IFN-g), interleukins (lL-2 & IL-4), immunoglobulins (lgA, IgM and IgG), concentrations were increased significantly in all CHC patients groups while, albumin, albumin/globulin ratio (AIG ratio), platelets count, multivariate disriminant analysis (MDA) (based on 4 variables, AST/ALT,platelets, ALP & albumin), were decreased significantly in all CHC patients groups compared to the control group. AST/ALT ratio increased in all groupsexcept GroupII.CD4+%wasignificantly low in Group III and Group IV, while CD8+% decreased significantly in Group II & Group IV.It was concluded that biochemical tests in combination with each other could diagnose serious pathological disorders. Furthermore, immune parameters possibly play a role in the degradation process of the liver. Although, immune system components contribute to the liver injury, they maintain low viral load in advanced stages.
Keywords: Chronic hepatitis C; liver function; immune system